Sectarianism and Fragmentation in the Muslim World: A Qur'anic and Hadith Perspective on the Causes, Consequences, and Path to Unity - Haruna, Salum Mussa (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
This study explores the historical and contemporary sectarian divisions within the Muslim world, particularly the Sunni-Shia split, and their political, social, and economic consequences. The research is motivated by the persistent fragmentation of the Muslim Ummah, which has weakened its global influence and made Muslim nations more susceptible to external interference. The study aims to analyze the root causes of sectarianism, assess its impact on the socio-political landscape of Muslim countries, and propose strategies for fostering unity. Using a qualitative research approach, including historical analysis and textual interpretation of Qur'anic and Hadith teachings, this study examines case studies from various Muslim nations to evaluate the real-world implications of sectarian divisions. The findings highlight that disunity among Muslim communities stems not only from theological differences but also from political rivalries and external interventions. Islamic principles such as wahda (unity), ukhuwah (brotherhood), shura (consultation), and adl (justice) provide a strong foundation for overcoming these divisions and strengthening the Ummah's collective sovereignty. This study recommends fostering inter-sectarian dialogue, promoting mutual understanding, and establishing cooperative frameworks among Muslim nations, particularly between influential countries such as Saudi Arabia and Iran. Future research should explore practical mechanisms for implementing these strategies at institutional and governmental levels and the role of Islamic education in countering sectarian narratives. Strengthening unity through Qur'anic values and Prophetic guidance can enhance the Muslim world's resilience, dignity, and autonomy in the face of global challenges.